REPRESENTASI KEKERASAN TERHADAP PEREMPUAN DALAM FILM VINA: SEBELUM 7 HARI (ANALISIS SEMIOTIKA CHARLES SANDERS PEIRCE) - SATRIA WIJAYA DEWA SAPUTRA; Nunik Hariyani; Veny Ari Sejati (JIKE: Jurnal Ilmu Komunikasi Efek, 2025)
This study investigates how violence against women is depicted in the film Vina: Sebelum 7 Hari (2024) using Charles Sanders Peirce’s semiotic approach. The film tells the story of Vina, a woman who becomes a victim of physical, sexual, and psychological violence by a motorcycle gang. The purpose of this research is to uncover how violence against women is represented through visual and narrative symbols in the film, as well as to deepen the understanding of how media shapes public perceptions of gender-based violence. The methodology used is a descriptive qualitative approach, analyzing scenes that depict violence against women using Peirce’s semiotic theory, which includes representamen, object, and interpretant. The findings of the study reveal that the film portrays violence not only as an individual act but also as a manifestation of the patriarchal social structure that normalizes male domination over women. This research contributes to the development of literature on the representation of violence in the media and emphasizes the importance of raising awareness about violence against women.